Following the Breadcrumbs: Jesus as Superfluous to Salvation? A Catholic Search - Admirand, Peter (Studies in Christian-Jewish Relations, 2020)
In this personal reflection and analysis, I, as a Catholic theologian, grapple with the haunting theological question of Jewish scholars, David Patterson and David Berger: Is Jesus, for Jews, “superfluous to salvation?” In light of major advances in Christian-Jewish relations and dialogue, most recently in the 2015 Vatican document, “The Gifts and Callings Are Irrevocable,” I seek to follow and assess where the (theologically rich) breadcrumbs lead me. Context and personal narrative become the first path as I trace how and why I reached their question—and my deep need to try to answer it, amidst a wounded, if not broken Church, still reeling from the child abuse scandal, among other ills. I then turn to Peter Phan’s interfaith Christology as presented in The Joys of Religious Pluralism—an important touchstone book—to acknowledge how a change in the papacy from Benedict to Francis can be seen as opening up, if not momentarily avoiding, the over-policing of certain theological pathways. I then return to Berger and Patterson’s question in the conclusion which they ask in “fear and ‘trembling.”